Analisis Penerapan Prinsip TQM (Total Quality Management) dalam Manajemen Pembiayaan Pendidikan oleh Komite Sekolah di SMPN 60 Bengkulu Utara - Khoirul Anwar; Istiana Istiana; Herwan Herwan; Fadila Azahra; Abdul Hamid (Lentera: Jurnal Ilmiah Kependidikan, 2025)
This study aims to analyze the implementation of Total Quality Management (TQM) principles in education financing management by the School Committee at SMPN 60 Bengkulu Utara. Using a descriptive qualitative approach with field research design, data were collected through in-depth interviews, observations, and documentation. Data analysis was conducted using the Miles and Huberman interactive model. The results indicate that the School Committee has implemented TQM principles through the PDCA (Plan-Do-Check-Act) cycle. The planning stage is carried out participatively based on needs analysis (customer focus), budget execution prioritizes learning quality with transparency principles, and evaluation is conducted periodically to ensure continuous improvement. The main supporting factors are effective communication between the school and the committee as well as clear regulations, while the inhibiting factors include the diverse economic conditions of parents and limited financial management competence of committee members. This study concludes that the integration of TQM in education financing can increase accountability and public trust, although it requires sustainable human resource capacity building.